The Influence of the Discovery Learning Model Assisted by Articulate Storyline on Students' Mathematical Resilience - Abel Garcia Arlis; Yerizon; Muhammad Zaini (Rangkiang Mathematics Journal, 2026)
This research seeks to examine how the Discovery Learning approach, when supported by Articulate Storyline, impacts students' resilience in mathematics. In an educational landscape rapidly evolving due to technological progress, a key priority for educators is to leverage ICT advancements to elevate teaching and learning standards. This research was conducted at SMAN 2 Rambatan on grade XI students, focusing on mathematics subjects, especially inverse functions and function composition. A quasi-experimental model was applied, structured around a nonequivalent control group design that collected data solely through posttests. Respondents comprised 51 students, divided into experimental (26) and control (25) groups. Data were collected using a 30-item instrument designed to evaluate resilience in mathematics. The analysis revealed that the Discovery Learning model, when supported by Articulate Storyline, significantly enhanced students' mathematical resilience compared to traditional teaching methods (p = 0.031). This finding confirms the importance of developing mathematical resilience through interactive and technology-based learning approaches, which can help students face challenges in the mathematics learning process. This study advances the development of innovative instructional strategies to enhance student academic performance within the framework of 21st-century education.